Brief Review on: Physical, Chemical and Functional Properties of Dammar - Noryawati Mulyono; Anton Apriyantono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Dammar is one of Indonesian forestry products which is abundant. It has unique physical, chemical and functional properties. The important physical properties of dammar include its solubility in some organic solvents, softening temperature, viscosity and its absorbance. The important chemical properties reviewed here include its properties as resin, composition of terpenoid compounds present in dammar, and essential oil yielded from distillation of fresh dammar. Physical and chemical properties of dammar need to be studied further in order to optimize its functional properties. So far, dammar is widely used as weighting agent and source of essential oil. However, now, some species of dammar are being explored and developed for sal flour, fat source, triacylglycerol substituent for cocoa butter and wood preservatives. Key words: Resin, terpenoid, essential oil, weighting agent.